Scale development of value co-destruction behavior in tourism. (October 2020) - Guan, Xinhua; Gong, Jinhong; Xie, Lishan; Huan, Tzung-Cheng
Abstract: Value co-destruction has received widespread attention from the tourism academic community. This article uses the employees and customers of tourism service providers as the main research objects and employs interviews and questionnaires to develop an employee-customer perspective measurement scale of value co-destruction behavior in tourism. The reliability analysis, exploratory factor analysis, confirmatory factor analysis, and structural equation model testing results show that the measurement scale of value co-destruction behavior in tourism consists of 5 dimensions (bad interpersonal communication behavior, bad information interaction behavior, irresponsible customer behavior, employee contract violation behavior, and irresponsible employee behavior) and a total of 29 items with high reliability, convergent validity, and discriminant validity, which can be used to evaluate the extent to which a subject abuses his or her own resources or the resources of others in tourism interactions, resulting in tourism value reduction or destruction. Finally, the research results and future research are discussed. Highlights: Value co-destruction (VCD) behavior receives attention from tourism academia. This study develops an employee-customer scale of VCD behavior in tourism. The scale of VCD behavior in tourism consists of 5 dimensions and 29 items. Attention should be paid to interpersonal, information and responsibility.